(3QSGdI aj eYGfi GdESJYGQGJ hCbSGegG hbQGFfgGs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO aEf eYGfi GdGSJYGQGJ heG jJYdb HgG bO PcQJ ai GdcJH eaUdI YSjQI GdVHW aCQOJ PcQgG eLedI eVHhWI Ydi hLg fWb Hg cJH GdeJbOejf s
(3BNQgG (B:s
(3hhLg GdaQb Hjf eG jLYd bQjfI GdecfjI hjLYd faSg JNjjdkG hHjf eG jLYd RGjGOkG YdjgG hJQTjMkG bhg GdENJUGU HGdeTHg Hg JeJ HMeO Gddg hYhfg hMSf Jhajbg hGdMeO ddg QH GdYGdejf Bejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs